Enhancing Financial Stability through Islamic Financial Planning: Literacy, Trust, and Investment Strategies in Indonesia - Kusmantari, Astri Asih (Baca Dulu Publisher, 2024)
This study examines strategies for enhancing financial stability through Islamic financial planning in Indonesia, focusing on the role of financial literacy, trust, and investment behaviors. Using a qualitative descriptive method and a literature review approach, the study analyzes key factors influencing saving and investment decisions in Islamic finance. Findings indicate that Islamic financial literacy significantly impacts financial behavior, enabling individuals to make ethical and Sharia-compliant decisions, particularly in utilizing instruments such as sukuk, mudharabah, and musharakah. Education and religiosity are also pivotal, driving higher participation in Islamic financial products. Moreover, trust and transparency in Islamic financial institutions enhance public confidence, encouraging active engagement in the sector. Sukuk is the preferred investment instrument due to its stability, while mudharabah and musharakah attract those seeking higher returns despite inherent risks. The study highlights the importance of improving Islamic financial literacy and transparency to bridge the gap between idealism and practice, ensuring that financial planning aligns with ethical and spiritual values. These findings offer valuable insights for policymakers, financial institutions, and researchers aiming to promote sustainable financial stability within Sharia frameworks.